A Research on the Role and Attitude of Lok Adalats in the Justice System of India: A Review: Exploring the Role and Challenges of Lok Adalats in the Indian Justice System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Constitution of India has characterized and announced to secure to every one of the subjects of India, Justice-social, monetary and political freedom equity and society as the shared objective for its nationals. The unceasing estimation of constitutionalism lies in the Rule of Law, which has three aspects Rule by Law, Rule under Law and Rule as indicated by Law. The literal translation of the Hindi moniker, Lok Adalat, is ‘People’s Court’- Lok, means people, and Adalat means court. Hence, simply it means a court for the people, by the people, and of the people themselves. Indian Judiciary is moving towards a time when it will be impossible for the courts to cope up with the dockets. If something is not done, the result will be a production of line of justice that none of us would want to see. The institution of Lok Adalat has evolved as one of the most important modes of alternative dispute resolution. The first instance of a Lok Adalat system was in 1982, in the village of Una, in the district of Junagarh, Gujarat. Though this was in its developing stage, a fairly modern version of the Lok Adalat system that exists till date began in Chennai, in 1986. The institution has developed, since, by leaps and bounds, by the people themselves, in order to provide for equitable justice speedily at minimal cost. The crux of this mode of justice dispensation is that it is contrived to enable the common man to ventilate his grievances against other citizens or even state agencies, and successfully arrive at an amicable settlement. Lok Adalats are a blend of all three forms of traditional ADR arbitration, mediation, and conciliation. Therefore, the researcher had undertaken this subject for contributing to the concept and explaining the difficulties in implementation and suggesting appropriate solutions for effective implementation of Lok adalat system.